Analysis of δ13C in lake sturgeon (Acipenser fulvescens [Rafinesque 1817]) fin and muscle tissue: an application of three arithmetic lipid correction models. (December 2014) - Braun, D.; Phillips, I. D.; Wissel, B.
Summary For stable isotope diet studies, fin tissue is preferred over muscle tissue because it is less intrusive and avoids unnecessary stress or mortality, particularly in endangered species, such as lake sturgeon (Acipenser fulvescens). Yet to ensure accurate analysis of lake sturgeon feeding habits the development of a muscle‐fin tissue fractionation factor is essential to remove lipid bias within different tissue types. We corrected for lipids in muscle and fin tissue by using three mathematical correction methods on 87 lake sturgeon from the Saskatchewan River in Saskatchewan, Canada from May to October 2011 (weight range: 0.60–43.30 kg; fork length range: 0.42–1.62 m). The mean respective fractionation factor for McConnaughey and McRoy (Mar. Biol., 53, 1979, 257) and Fry et al. (Estuaries, 26, 2003, 82) models were not significantly different from each other (P > 0.05, 0.86 and 0.80‰), and neither significantly differed from a 1 : 1 line (slope = 0.97, r2 = 0.80 and 0.81, respectively). Conversely, the Post et al. (Oceologia, 152, 2007, 179) model results were significantly different from the 1 : 1 line with a low r2 of 0.19 and a fractionation factor significantly different from the other two models (P < 0.05, 2.81‰), which was a result of a non‐linear increase in fractionation factor with C : N values. Therefore, of the three correction factors tested, McConnaughey and McRoy (Mar. Biol., 53, 1979, 257) and Fry et al. (Estuaries, 26, 2003, 82) are both acceptable models when correcting for lipid bias in lake sturgeon tissues. However, we preferred the Fry et al. (Estuaries, 26, 2003, 82) formula because of its mass balance approach and minimal alterations when applied to a new species.